1893 R.I. Pub. Laws 231 - (:unkn) unknown (My University, 1893)
Ch. 1180, § 1: Prohibited the carrying of any dirk, Bowie knife, butcher knife, dagger, razor, sword cane, air-gun, billy, metal knuckles, slungshot, pistol, or firearm of any description concealed upon his person.
Keywords: CARRY; CARRY - CONCEALED